THE INFLUENCE OF ENVIRONMENTAL PERFORMANCE, ENVIRONMENTAL INFORMATION DISCLOSURE, ENVIRONMENTAL COSTS ON COMPANY VALUE (CASE STUDY OF A MINING COMPANY) - Crescentiano Agung Wicaksono; Rahandhika Ivan Adyaksana; Rifai Ahmad Harkas (STABILITY : Journal of Management and Business, 2025)
This research is driven by the increasing focus on corporate sustainability practices, especially within the mining sector, which significantly impacts firm value The purpose of the study is to examine the effect of environmental performance, environmental information disclosure, and environmental costs on firm value. The study employs a quantitative approach using secondary data obtained from the annual and sustainability report of mining companies listed on the Indonesia Stock Exchange during the 2019-2023 period. The sample was selected using a purposive sampling method with a total of 74 observation. The result show that environmental performance has on significant effect on firm value, while environmental information disclosure has a significant positive effect and environmental costs have a significant negative effect on firm value. These findings indicate that transparent environmental disclosure can enhance investor confidence, where as environmental costs are still perceived as a financial burden. This study contributes theoretically by strengthening signaling theory and provides practical implications for companies to balance sustainability strategies with cost sufficiency.